Demands for real and financial assets in Botswana - Philippa S. Dee (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
Traditionally, asset demands are derived as a solution to the individual's or household's problem of allocating wealth among various real and financial alternatives. The demand for each asset depends on the own real rate of return, but also on the real rates of return to alternative assets. The sensitivity to own and cross rates captures the speculative element in portfolio allocation, the motive usually being to maximise end-of-period wealth. Typically, asset demands also depend on income, reflecting the transactions motive for asset holding. These determinants are generally the same, whether the asset choice is seen to take place under conditions of risk or certainty.
Keywords: 330